Iowa RBA, December 18, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for December 18, 1995. Highlights of the update include sightings of a Black-billed Magpie, Snowy Owl, Evening Grosbeak, Townsend's Solitaire, Glaucous Gull and a Northern Mockingbird. Birds sighted include species from five Christmas counts. Also included are handwritten notes for the next week's update with sightings of a Golden Eagle and a Common Redpoll. Epson - sheet feed/flatbed